EFEKTIVITAS PEMBELAJARANÂ PENDIDIKAN JASMANIÂ MELALUI PENDEKATAN MODIFIKASI PERMAINAN BOLAVOLI (STUDI PADA SISWA KELAS VIII SMPN 1 NGANCAR KEDIRI ) - LIYA SAKARINA SARI, MELSA (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract There are many factors which affect the low learning achievement of the students and the low effectiveness of learning physical education. One of them is the physical education sport and health teachers have less creativity in creating and developing learning strategy. A strategy which can be used by teacher to be able to implement the game models that have been modified to motivate the students in following the physical education learning. Modification is an effort which is done by the teachers in order to pay attention to the changes in students’ ability and help encouraging those changes. The objectives of this research are: 1) to find out the effect of volleyball game modification toward the learning of physical education sport and health on the eighth graders of SMPN 1 Ngancar Kediri; 2) to determine how far the effect of volleyball game modification toward the effectiveness of learning physical education sport and health on the eighth graders of Junior High School 1 Ngancar Kediri. Target of the research are the eighth graders of Junior High School 1 Ngancar Kediri and numbers taken are 30 students. This research belongs to experimental research with the descriptive quantitative approach. Data collection technique is done by using Formative Class Evaluation questionnaires and physical education observation sheets. The result of the research: the FCE average score before the learning is 2, 73 (catagorize as good), while the result after the learning is 2, 87 (categorize as very good). Those results show that there is improvement on the result of students’ FCE (pre test and post test) as 5, 01%. The result of t-test shows that tcount 4,247 > ttable 2,045. With 5% significancy degree. It can be concluded that: (1) there is significant effect from the modification of volleyball game toward the effectiveness of learning physical education sport and health on the eighth graders of SMPN 1 Ngancar Kediri; (2) the physical education learning lesson using modification of volleyball game given affects the effectiveness of learning physical education sport and health on the eighth graders of SMPN 1 Ngancar Kediri as big as5, 01%. Keywords : Effectivity, Volleyball Modification, Physical Education.